Assessment of the pivot shift using inertial sensors - Zaffagnini, Stefano (Curr Rev Musculoskelet Med, 2016)
The pivot shift test is an important clinical tool used to assess the stability of the knee following an injury to the anterior cruciate ligament (ACL). Previous studies have shown that significant variability exists in the performance and interpretation of this manoeuvre. Accordingly, a variety of techniques aimed at standardizing and quantifying the pivot shift test have been developed. In recent years, inertial sensors have been used to measure the kinematics of the pivot shift. The goal of this study is to present a review of the literature and discuss the principles of inertial sensors and their use in quantifying the pivot shift test.